Knowledge, attitudes and practice questionnaires in dengue, Zika, chikungunya and yellow fever settings: a scoping review protocol - Kate Zinszer; Bouchra Nasri; Daniel Szaroz; Claudia Ximena Robayo González (BMJ Open)
Introduction Arboviruses are a broad classification of viral pathogens that require vectors such as mosquitoes for infection transmission. The burden of arboviral diseases worldwide is substantial, affecting millions of people annually, with the Aedes aegypti mosquito responsible for spreading several common arboviruses, including dengue, chikungunya, Zika and yellow fever. One public health strategy to control and prevent these viruses is to influence community members’ behaviours related to reducing the breeding sites of Aedes mosquitoes, and knowledge, attitudes and practice (KAP) questionnaires are often used as part of these education campaigns.Objectives To explore the content of KAP questionnaires and methodologies used to evaluate arboviral infections, focusing on dengue, Zika, chikungunya and yellow fever.Methods and analysis To identify and describe KAP questionnaires for the selected arboviral infections, a scoping review will be performed and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Scoping Review Extension guidelines. Scientific databases such as MEDLINE, Cochrane, EMBASE, Web of Science, Scielo and LILACS will be searched systematically. Two independent reviewers will screen the title and abstract, followed by a full-text review of the selected articles using the COVIDENCE platform. The extracted information will include citation details, the type of arbovirus, the type of questions in each domain, the scoring system, the theoretical framework and the statistical analysis. The results will be presented comprehensively in tables and figures.Ethics and dissemination Ethics approval is not required. Knowledge transfer will be conducted through conference presentations and publications.